The rise and fall of retail banking model in Asia - li, Juncheng (2017)
This dissertation studies the rise and fall of the Asian retail banking industry. To achieve the research purpose, this research has incorporated the qualitative research approach, specifically in-depth interview which was carried out among 6 managerial employees from OCBC, BOC, ICBC, HSBC and CIMB which are major banks in Asia. As a result, this research finds that the growth and development of the Asian banking industry is facilitated by technological integration, product innovation and multi-channel distribution strategy. However, the emergence of new financial services providers specifically fin tech, shrinking deposits and sluggish economic situation in Asia have impacted the competitive advantage of the Asian banking industry. In the context of the measures which should be incorporated by the retail banks to facilitate long term sustainability, this research suggests that Asian retail banks should incorporate technological development, optimize product features and incorporate big data technology. In a nutshell, this research provides implications regarding context associating the rise and fall of the Asian retail banking industry.